Discovery of new thymol-3,4-disubstituted thiazole hybrids as dual COX-2/5-LOX inhibitors with in vivo proof - Mostafa M. M. El-Miligy; Ahmed K. Al-Kubeisi; Rasha A. Nassra; Saad R. El-Zemity; Aly A. Hazzaa (Taylor & Francis Group, 2024)
AbstractNew thymol-3,4-disubstitutedthiazole hybrids were synthesised as dual COX-2/5-LOX inhibitors. Compounds 6b, 6d, 6e, and 6f displayed in vitro inhibitory activity against COX-2 (IC50= 0.037, 0.042, 0.046, and 0.039 µM) nearly equal to celecoxib (IC50= 0.045 µM). 6b, 6d, and 6f showed SI (379, 341, and 374, respectively) higher than that of celecoxib (327). 6a-l elicited in vitro 5-LOX inhibitory activity higher than quercetin. 6a-f, 6i-l, 7a, and 7c possessed in vivo inhibition of formalin induced paw edoema higher than celecoxib. 6a, 6b, 6f, 6h-l, and 7b showed gastrointestinal safety profile as celecoxib and diclofenac sodium in the population of fasted rats. Induced fit docking and molecular dynamics simulation predicted good fitting of 6b and 6f without changing the packing and globularity of the apo protein. In conclusion, 6b and 6f achieved the target goal as multitarget inhibitors of inflammation.